Deuterium excess and 17O-excess variability in meteoric water across the Pacific Northwest, USA. Issue 1 (1st January 2020) - Bershaw, John; Hansen, Dougal D.; Schauer, Andrew J.
Abstract: High-precision triple oxygen isotope analysis of water has given rise to a novel second-order parameter, 17 O-excess (often denoted as Δ 17 O), which describes the deviation from a reference relationship between δ 18 O and δ 17 O. This tracer, like deuterium excess (d-excess), is affected by kinetic fractionation (diffusion) during phase changes within the hydrologic cycle. However, unlike d-excess, 17 O-excess is present in paleowater proxy minerals and is not thought to vary significantly with temperature. This makes it a promising tool in paleoclimate research, particularly in relatively arid continental regions where traditional approaches have produced equivocal results. We present new δ 18 O, δ 17 O, and δ 2 H data from stream waters along two east–west transects in the Pacific Northwest to explore the sensitivity of 17 O-excess to topography, climate, and moisture source. We find that discrepancies in d-excess and 17 O-excess between the Olympic Mountains and Coast Range are consistent with distinct moisture source meteorology, inferred from air-mass back trajectory analysis. We suggest that vapor d-excess is affected by relative humidity and temperature at its oceanic source, whereas 17 O-excess vapor is controlled by relative humidity at its oceanic source. Like d-excess, 17 O-excess is significantly affected by evaporation in the rain shadow of the Cascade Mountains, supporting its utility as an aridity indicator in paleoclimate studies where δ 2 H data are unavailable. We use a raindrop evaporation model and local meteorology to investigate the effects of subcloud evaporation on d-excess and 17 O-excess along altitudinal transects. We find that subcloud evaporation explains much, but not all of observed increases in d-excess with elevation and a minor amount of 17 O-excess variation in the Olympic Mountains and Coast Range of Oregon. Key Points: 17 O-excess correlates spatially with relative humidity across the Pacific Northwest, supporting its use as an aridity indicator in paleoclimate studies. Discrepancies in d-excess and 17 O-excess between the Olympic Mountains and Oregon Coast Range suggest that their moisture source is different. Subcloud evaporation explains most of observed increases in d-excess with elevation, and a minor amount of 17 O-excess variation in the Olympic Mountains and Oregon Coast Range.